Assessment of the distribution of phenolic compounds and contribution to the antioxidant activity in Tunisian fig leaves, fruits, skins and pulps using mass spectrometry-based analysis. Issue 12 (21st September 2015) - Ammar, Sonda; del Mar Contreras, María; Belguith-Hadrich, Olfa; Segura-Carretero, Antonio; Bouaziz, Mohamed
Abstract : The qualitative and quantitative phenolic composition explains the differences in the antioxidant activity of fig leaves, fruits, pulps, and skins. Abstract : The phenolic composition of leaves, fruits, skins and pulps from two F. carica cultivars, 'Temri' and 'Soltani', was studied in order to understand its contribution to the antioxidant activity. A total of 116 compounds were characterized based on the results obtained by reversed-phase ultra-high performance liquid chromatography coupled to diode array and mass spectrometry detection. In general, the leaves of both cultivars and the skin of 'Soltani' presented richer qualitative profiles compared to the other plant parts. Using the negative ionization mode, qualitative profiles of the same part of the studied figs were similar. In this regard, rutin was the main compound in fruits, skins and leaves, but with different relative amounts. Alternatively, an isomer of prenylhydroxygenistein was the major compound in the pulps. In the positive ionization mode, 9 anthocyanins were characterized in 'Soltani' skin, only two of them being also present in the green cultivar 'Temri'. The main anthocyanins were cyanidin 3-rutinoside and cyanidin 3, 5-diglucoside, depending on the cultivar and fruit part. In this ionization mode, 15 furanocoumarins were also detected in the leaves of both the studied cultivars with methoxypsoralen and psoralen being the most relatively abundant. In addition, our findings showed a good correlation between the antioxidant activity, total phenol content, and abundance of some phenolic subfamilies such as hydroxybenzoic acids, flavonols, flavones, hydroxycoumarins and furanocoumarins with r > 0.97.